Numb : a novel - Ferrell, Sean (HarperPerennial, 2010)
A man with no memory who feels no pain, Numb travels to New York City after a short stint with the circus, following the one and only clue he holds to his hidden history: a brittle, bloodstained business card. But once there, word of his condition rapidly spreads - sparked by the attention he attracts by letting people nail his hands to wooden bars for money - and he quickly finds himself hounded on all sides by those who would use his unique ability in their own pursuits of fame and fortune.